Knowledge, practice, and barriers of optimal mask usage among general public – A cross-sectional study from Kerala, South India - Ashok, Aditya; Kunoor, Akhilesh; Rajeev, Midhun; Melepurakkal, Soumya; Aravind Mohankumar Syamala,; Venugopal, Sarath; Vishnu Gopalakrishnan,; Tajik Muhammed Shafi, (Asian Journal of Medical Sciences, 2022)
Background: Social distancing, mask, and sanitizers are advised to cut the chain of transmission of the droplet and airborne infection since the first case of COVID-19 was reported from Wuhan. Universal mask usage is advised by the center for disease control. Despite this, it is assumed that there is no adequate mask practice. Aims and Objectives: The objectives of the study are as follows: (1) To assess the knowledge and practice regarding optimal mask usage in a different setting by the general community. (2) To identify the barriers for optimal mask usage as experienced by users. Materials and Methods: We did a cross-sectional study in Kerala using self-made validated questionnaire translated to Malayalam, the regional language distributed by web based Google form. The sample size was calculated as 200 with an assumption of awareness regarding mask usage among the general public to be at least 60% with a confidence interval of 95 and allowable error of 10% Knowledge was considered as high if 80–100%, moderate if 60–79% and low if 0–59%. The practice was considered as good if >75, 74–50 satisfactory and if <50, it is termed as unsatisfactory. Results: Overall knowledge regarding masks and their usage was 52. 88% which is low. Only 38% were doing satisfactory practice. There were lacunae in knowledge regarding mask reusage (39.9%), ideal masks in hospital settings (43.3%). Only 26.4% practiced optimal method of mask removal and 38.4% safe mask disposal. Major barriers for mask usage were suffocation (49.3%) and exertional dyspnea (46.9%). Conclusion: More awareness needs to be created among the public for COVID appropriate behavior with a focus on mask usage. There is a need to address the commonly observed barriers for adhering to mask practice.